Quantum of cortico-cancellous bone safe for harvest from anterior iliac wing of pediatric patients: a finite element analysis with clinical correlation - Tarun, Swetha; Pendem, Sneha; Raja, Krishna Kumar (International Surgery Journal, 2020)
Background: Objective was to assess the maximum quantum of cortico- cancellous bone that can be harvested from the Anterior Iliac Wing (AIW) of paediatric population. Methods: All patients reporting to the unit for the correction of bilateral cleft alveolus were included. A Computed Tomogram (CT) of the hip was recorded and the volume of cancellous bone available for harvest was assessed. Finite element model of the hip was generated using D2P and Geomagic Free form software and the impact of bone harvest on stress distribution along the anterior iliac wing was assessed by substituting the muscle forces (hip abductors and sartorius group) and was clinically correlated to volume harvested and donor site morbidities. Results: 10 patients were enrolled, 5 patients were excluded. CT volumetric evaluation revealed an average 0.5 cc to 4.7 ccof cancellous bone and 6.7 cc to 11 cc of cortical bone was available for harvest. Harvest of 50% of available graft volume was safe with minimal stress distributed along the line joining the tuberosity to the area between Antero Superior and Inferior spines (4.2 MPa at rest and 18.5 MPa at stance). The stress levels increased with increase in volume of bone harvested. Intra operatively 1.9 cc to 6.2 cc of cortico cancellous graft was harvested, which was equivalent to 60% of the graft available with no long-term morbidities. Conclusions: The volume of bone graft harvest should be restricted (up to 6 cc) to avoid long term morbidities.